Politics of Urban Planning and Inclusive Development in Tanzania - Ruhangisa, Valentine Flavian (PT. Riset Press International, 2026)
Urban planning and inclusive development have become important issues to the fast urbanization and socioeconomic change of Tanzania. The politics of city governance, the spatial planning and fair allocation of services has remained to impact on the way cities develop and operate. The paper provides an analysis of the impact of the governance structure, politicking interests, and policy implementation on the outcomes of urban development in major cities in Tanzania, namely, Dar es Salaam, Dodoma, Arusha, and Mwanza. It relies on theories of institutional and governance and examines their overlapping to ensure inclusiveness or not through decentralization, political accountability, and participatory planning frameworks. Based on evidence through government reports, academic research and reviews of urban policies, the paper indicates that gaps between policy design and policy implementation occur continuously with political interference, institutional failures and low citizen participation. Although there are progressive policies of urban development like the National Urban Development Policy (2012) and the Tanzania Development Vision 2025, they have not been implemented due to the lack of proper resources and effective coordination between the central and local governments. The paper concludes that to attain inclusive urban development in Tanzania, the government should strengthen transparency in governance, increase the autonomy of local governments and promote the multi-stakeholder participation in the urban planning processes.